A Collective Case Study of African American Male Athletic Directors’ Leadership Approaches to Diversity in College Sport - Singer, John N.; Cunningham, George B. (Journal of Intercollegiate Sport, 2018)
The primary purpose of this research was to garner an understanding of how African American male athletic directors manage diversity and inclusion in their college athletic departments. The authors conducted a collective qualitative case study of two major university athletic departments that each had an African American male athletic director. The authors conducted interviews, took field notes, and analyzed relevant documents/artifacts, all of which served as data sources. Results indicate these leaders viewed diversity and inclusion as (a) increasing racial and gender minority representation in leadership positions and (b) utilizing this diversity as a mechanism for role modeling and mentoring. Differences between the leaders also emerged, as one explicitly focused on conducting an organizational analysis and on making diversity training mandatory for all employees, while the other did not engage in these activities. The authors discuss contributions to the literature and future directions for research.